Characteristics of the Problem of Implementing Solid Waste Policy in Rappocini District, Makassar City - Kasmita, Maya; Tahmir, Suradi; Rifdan, Rifdan; Wardah, Siti Syarifah Wafiqah (Pinisi Business Administration Review, 2022)
The implementation of the solid waste policy in Rappocini District, Makassar City is a government step in overcoming the solid waste problem in Makassar City, especially in Rappocini District. This research focuses on the characteristics of the existing problems. The process of determining the characteristics of policy problems almost always involves the norms of legislation, local wisdom, physics formulas and others. In the policy characteristics, there are problems in the level of technical difficulty of the existing problems, the level of pluralism of the target group and the percentage of the target group to the total population. Often policy problems get solutions by decision-making groups. With descriptive qualitative research describes the problems that exist in relation to the implementation of waste management policies in Makassar City and then analyzes them to an absolute conclusion. This research uses a case study approach involving certain communities as research subjects.